Antimicrobial resistance profiles and oxacillinase genes in carbapenem-resistant Acinetobacter baumannii isolated from hospitalized patients in Santa Catarina, Brazil - Giselle Dall Cortivo; Andréia Gutberlet; Jéssica Augustini Ferreira; Leslie Ecker Ferreira; Roseneide Campos Deglmann; Glauco Adrieno Westphal; Paulo Henrique Condeixa de França (Revista da Sociedade Brasileira de Medicina Tropical, 2015)
Abstract: INTRODUCTION: Carbapenems are the therapy of choice for treating severe infections caused by the Acinetobacter calcoaceticus-Acinetobacter baumannii complex. We aimed to assess the prevalence and antimicrobial susceptibility profiles of producers of distinct oxacillinases among nosocomial isolates of the A. calcoaceticus-A. baumannii complex in a 249-bed general hospital located in Joinville, Southern Brazil. METHODS: Of the 139 A. baumannii clinical isolates with reduced susceptibility to carbapenems between 2010 and 2013, 118 isolates from varying anatomical sites and hospital sectors were selected for genotypic analysis. Five families of genes encoding oxacillinases, namely blaOXA-23-like, blaOXA-24-like, blaOXA-51-like, blaOXA-58-like, and blaOXA-143-like, wereinvestigated by multiplex polymerase chain reaction (PCR). RESULTS: Most (87.3%) isolates simultaneously carried the blaOXA-23-likeand blaOXA-51-likegenes, whereas three (2.5%) isolates harbored only blaOXA-51-likeones. The circulation of carbapenem-resistant isolates increased during the study period: from none in 2010, to 22 in 2011, 64 in 2012, and 53 in 2013. CONCLUSIONS: Isolates carrying the blaOXA-23-likeand blaOXA-51-likegenes were widely distributed in the hospital investigated. Because of the worsening scenario, the implementation of preventive measures and effective barriers is needed.